Land‐use intensity impacts habitat selection of ground‐nesting farmland birds in The Netherlands. Issue 1 (5th January 2023) - Li, Yuhong; Piersma, Theunis; Hooijmeijer, Jos C. E. W.; Howison, Ruth A.
Abstract: Agricultural intensification has modified grassland habitats, causing serious declines in farmland biodiversity including breeding birds. Until now, it has been difficult to objectively evaluate the link between agricultural land‐use intensity and range requirements of wild populations at the landscape scale. In this study of Black‐tailed Godwits Limosa limosa, we examined habitat selection and home range size during the breeding phase in relation to land‐use intensity, at the scale of the entire Netherlands. From 2013 to 2019, 57 breeding godwits were tracked with solar‐Platform Transmitter Terminals (26–216 locations [mean: 80] per bird per breeding phase) and used to estimate their core (50%) and home ranges (90%). Of these, 37 individuals were instrumented in Iberia and therefore unbiased toward eventual breeding locations. The tracks were used to analyse habitat selection by comparing the mean, median and standard deviation of land‐use intensity of core and home ranges with matching iterated random samples of increasing radii, that is, 500 m (local), 5 km (neighbourhood), 50 km (region) and the whole of The Netherlands. Land‐use intensities of the core and home ranges selected by godwits were similar to those at the local and neighbourhood scales but were significantly lower and less variable than those of the region and the entire country. Thus, at the landscape scale, godwits were selected for low‐intensity agricultural land. The core range size of godwits increased with increasing land‐use intensity, indicating high agricultural land‐use intensity necessitating godwits to use larger areas. This is consistent with the idea that habitat quality declines with increasing land‐use intensity. This study is novel as it examines nationwide habitat selection and space use of a farmland bird subspecies tracked independently of breeding locations. Dutch breeding godwits selected areas with lower land‐use intensity than what was generally available. The majority of the Dutch agricultural grassland (94%) is managed at high land‐use intensity, which heavily restricts the viability of breeding possibilities for ground‐nesting birds. The remote sensing methodology described here illustrates the potential to study entire wild populations from the local field level to their whole spatial range. Abstract : At the scale of the entire Netherlands, black‐tailed godwits (tagged with satellite transmitters on their stopover sites [ N = 37]) strongly selected for low‐intensity agricultural land, while high‐intensity land use remained largely unused. In addition, the core range size of breeding godwits increased with increasing land‐use intensity. Overzicht: Door de intensivering van de landbouw zijn grasland‐habitats veranderd, waardoor de biodiversiteit van landbouwgrond, inclusief broedvogels, ernstig is afgenomen. Tot nu toe was het moeilijk om het verband tussen de intensiteit van het landgebruik in de landbouw en de eisen die wilde populaties aan hun leefgebied stellen objectief te beoordelen op landschapsschaal. In dit onderzoek naar Grutto's ( Limosa limosa limosa ) hebben we de habitatkeuze en de grootte van het leefgebied tijdens de broedfase onderzocht in relatie tot de intensiteit van het landgebruik, op de schaal van heel Nederland. Van 2013 tot 2019 werden 57 broedende grutto's gevolgd met satellietzenders. Dit leverde 26 ‐ 216 bezochte plekken (gemiddeld: 80) per vogel per broedseizoen op. Hiermee konden we de omvang van het kern‐ (50%) en het overige leefgebied (90% van alle bezochte plekken) schatten. 37 individuen werden voorzien van een zender in Spanje of Portugal; daarvan hadden we dus geen voorkennis over de uiteindelijke broedlocaties. Om de habitatselectie te analyseren werd het gemiddelde, de mediaan en de standaarddeviatie van de landgebruiksintensiteit van kern‐ en overige leefgebieden vergeleken met overeenkomende herhaalde willekeurige steekproeven uit al het beschikbare habitat met toenemende stralen, d.w.z. 500 m (lokaal), 5 km (buurt), 50 km (regio) en heel Nederland. Landgebruiksintensiteiten van de door grutto's daadwerkelijk geselecteerde kern‐ en leefgebieden waren vergelijkbaar met die op lokaal en buurtniveau, maar waren significant lager en minder variabel dan die van de regio en het hele land. Grutto's kozen op landschapsschaal voor landbouwgronden met een lage gebruiksintensiteit. De grootte van het kerngebied nam toe naarmate de intensiteit van het landgebruik toenam. Dit suggereert dat grutto's grotere gebieden moesten gebruiken bij een hogere intensiteit van het landgebruik in de landbouw. Dit komt overeen met het idee dat de habitatkwaliteit afneemt naarmate de intensiteit van het landgebruik toeneemt. Grutto's hadden daardoor een groter gebied nodig om in al hun behoeften te voorzien. Deze studie is nieuw omdat het onbevooroordeeld landelijke habitatselectie en ruimtegebruik van een boerenlandvogel inzichtelijk maakt. In Nederland broedende grutto's selecteerden gebieden met een lagere landgebruiksintensiteit dan algemeen beschikbaar was. Het grootste deel van het Nederlandse landbouwgrasland (94%) wordt beheerd met een hoge landgebruiksintensiteit, wat de geschiktheid als broedplek voor grondbroedende vogels sterk beperkt. Dit onderzoek laat zien dat met behulp van "remote sensing" het mogelijk is om wilde populaties in z'n geheel te bestuderen, van het lokale perceelsniveau tot hun hele verspreidingsgebied.